Stability of unsaturated soil slopes under rainfall and seismic loading - Huang, Wengui (2018)
Rainfall and earthquake are the two main factors that can cause landslides in unsaturated soils. Earthquake loading is cyclic in nature. The effect of cyclic loading on the shear strength of unsaturated soils was investigated by conducting cyclic and monotonic simple shear tests. The main objective of this study is to develop equations that can easily be used for slope stability analysis considering the effects of rainfall and earthquake. To achieve the objective, an analytical framework for unsaturated slope stability analysis was developed first. More specifically, the conventional log-spiral upper bound limit analysis for dry and saturated soil slopes was extended to analyze the rotational failure of unsaturated soil slopes under rainfall. A translational failure mechanism in the context of upper bound plasticity theory was proposed to analyze the translational failure. Upper bound limit analysis can be efficiently used to develop slope stability charts. Through regression analysis of the stability numbers, stability equations were proposed for dry and saturated soil slopes, unsaturated soil slopes under rainfall and seismic loading. The accuracy of the proposed equations was validated with existing stability charts and numerical approach for a wide range of slope geometries and soil properties. Application of the proposed stability equations was illustrated by reanalyzing slope stability problems that have been solved by numerical methods and back analysis of landslides.